A Study on relationship between Workplace Fun culture and Job Satisfaction among IT Professionals - A.Jerina Bee, Dr. B.Vimala, (International Journal of Scientific Research and Management (IJSRM), 2014)
A work environment is made up of a range of factors, including company culture, management styles,hierarchies and human resources policies. Employee satisfaction is the degree to which employees feelpersonally fulfilled and content in their job roles. Employee turnover is the rate at which employeesleave their employers, whether voluntarily or involuntarily. These three distinct concepts areinseparably linked; workplace environments greatly influence employee satisfaction, which in turndirectly affects employee turnover rates. Knowing how to use a positive work environment to increaseemployee satisfaction is a key to developing a high-performance workforce. Company cultures must fitwith their employees to increase job satisfaction, or else employees may look elsewhere to find aworkplace better suited to their personalities.